Euphemisms in education: a semantic analysis in EIB - Canchari Samamé, Jennifer (2021)
In this research work, there is a semantic description of the use of euphemisms in the oral discourses of Intercultural Bilingual Education (EIB). The aim of this study is to explain the euphemistic expressions used in EIB discourses in Peru on the basis of conceptual metaphors involving euphemisms. For this purpose, a methodology related to cognitive linguistics is used to explain the meanings associated with these expressions. This analysis is qualitative and was carried out on the basis of data extracted from videos on IBE in Peru published on YouTube. From the sample obtained, it was possible to confirm that euphemisms increase the idea of belonging to a native community, emphasizing its own nature.